2022
DOI: 10.3389/feart.2022.943853
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Thermal Conductivity of Unsaturated Porous Media Deduced by Pore-Scale SPH Simulation

Abstract: The smoothed particle hydrodynamics (SPH) method was employed to simulate the heat transfer process in porous media at the pore scale. The effective thermal conductivity of a porous medium can be predicted through a simulation experiment of SPH. The accuracy of the SPH simulation experiment was verified by comparing the predicted values with reference values for ideal homogeneous media and multiphase layered media. 3D simulation experiments were implemented in granular media generated by the PFC method. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 40 publications
1
52
0
1
Order By: Relevance
“…Previous studies of the effect of temperature have focused mainly on concrete materials, granular soil, and fine clay (Chitambira, 2004;Bai et al, 2019Bai et al, , 2022, but few have examined soft clay containing organic matter. Gu et al (2018) reported silt in a river beach in Shenzhen, China, to contain up to 15.6% organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the effect of temperature have focused mainly on concrete materials, granular soil, and fine clay (Chitambira, 2004;Bai et al, 2019Bai et al, , 2022, but few have examined soft clay containing organic matter. Gu et al (2018) reported silt in a river beach in Shenzhen, China, to contain up to 15.6% organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research results show that the soil moisture content, temperature, and other factors will also have a great impact on the test results [22][23][24][25]. However, since the focus of this paper is on the composition of the new antisliding structure, the soil moisture content and temperature are set 6 Geofluids as a fixed value, and the following research results are explained based on this condition.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…e structural surface is the weak surface prone to damage in the rock mass. Recently, in addition to the experimental method [26,27], continuous constitutive modeling and discrete element method are increasingly used to simulate the deformation and failure of geotechnical materials [28][29][30][31][32][33][34][35][36][37]. e discrete element method has significant advantages in simulating cracks and large deformations.…”
Section: Microfracture and Joint Surface In Rockmentioning
confidence: 99%